Análise do material didático do curso de licenciatura em física da Universidade Federal do Ceará na modalidade de educação a distância. - Pereira, Caniggia Carneiro (2016)
The main objective of this research is to analyze the didactical materials used in the Undergraduated Course in Physics, focusing the teachers formation, in semipresential modality, checking the contribution of each element involved in the didactic transition of the material, based on the opinions of the students. The course is offered by the Federal University of Ceará (UFC), with management of UFC Virtual Institute. Specifically, we chose to analyze the disciplines that work directly with the Physics contents: Physics I, Physics II, Physics III, Physics IV, Modern Physics Topics, beyond the initial subjects of Mathematics, Mathematics I and Mathematics II. These disciplines usually present large failure rates and, as they are prerequisites for other disciplines of the program, the failure of students causes a considerable damming. Consequently, a small number of students reach the conclusion of the course in regular time. Initially, a large literature search was conducted in journals, websites and conference proceedings, seeking to find some works that dealt specifically with teaching materials for distance education courses. The teaching material was analyzed thoroughly and, a questionnaire, based on the Likert Scale, was applied to the students that answered it on line. The questionnaire took into account the didactical resources and didactic transition, analyzing the contributions of each resource for understanding the content and student learning. For its tabulation, we used the Middle Ranking technique. Complementing the data collection, interviews were conducted with the students. Through the joint discussion of the results of online survey realized with the students, both, by the interviews, as by direct analysis of the teaching material, we present an overview that describes the didactical material used in the Semipresential Physics Course of UFC. In the end, are given guidances to the application of research tool in other subjects and courses in order to promote the replicability of the knowledge produced.